The effect of pregnancy exercise on the sleep quality of pregnant women in the third trimester : A pre-experimental study - Pratiwi, Dewi Sari; Armayani, Armayani; Poddar, Ruma (Journal of Community Nursing and Primary Care, 2025)
Background: Sleep disturbances are commonly experienced by women during the third trimester of pregnancy due to physiological, hormonal, and anatomical changes that may negatively affect maternal comfort and fetal well-being. Non-pharmacological interventions, including pregnancy exercise, have been recommended to alleviate physical discomfort and improve sleep quality safely during pregnancy. Objective: This study aimed to examine the effect of pregnancy exercise on sleep quality among pregnant women in the third trimester. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 44 third-trimester pregnant women recruited using purposive sampling from the working area of Siotapina Public Health Center, Buton Regency, Indonesia. Sleep quality was assessed using a structured sleep quality questionnaire before and after the pregnancy exercise intervention. Descriptive statistics were used to summarize sleep quality distributions, and the Wilcoxon Signed Rank Test was applied to evaluate differences between pre-intervention and post-intervention sleep quality scores. Results: Prior to the intervention, the majority of participants experienced poor sleep quality, whereas after participating in pregnancy exercise the proportion of women reporting good sleep quality increased substantially. Statistical analysis demonstrated a significant improvement in sleep quality following the intervention (Z = −3.742; p < 0.001), indicating that pregnancy exercise effectively reduced sleep disturbances among pregnant women in the third trimester. Conclusion: Pregnancy exercise significantly improves sleep quality among women in the third trimester of pregnancy. Incorporating structured pregnancy exercise programs into routine antenatal care may help reduce sleep disturbances and enhance maternal well-being through safe, non-pharmacological interventions.